NFC-Based User Interface for Smart Environments - Susanna Spinsante; Ennio Gambi (Advances in Human-Computer Interaction)
The physical support of a home automation system, joined with a simplified user-system interaction modality, may allow people affected by motor impairments or limitations, such as elderly and disabled people, to live safely and comfortably at home, by improving their autonomy and facilitating the execution of daily life tasks. The proposed solution takes advantage of the Near Field Communications technology, which is simple and intuitive to use, to enable advanced user interaction. The user can perform normal daily activities, such as lifting a gate or closing a window, through a device enabled to read NFC tags containing the commands for the home automation system. A passive Smart Panel is implemented, composed of multiple Near Field Communications tags properly programmed, to enable the execution of both individual commands and so-called scenarios. The work compares several versions of the proposed Smart Panel, differing for interrogation and composition of the single command, number of tags, and dynamic user interaction model, at a parity of the number of commands to issue. Main conclusions are drawn from the experimental results, about the effective adoption of Near Field Communications in smart assistive environments.